The lady in white - Campbell, Colin (Cambridge English readers. Level 4, 1999)
John is a successful TV producer with a happy family life. He wants to make a programme about the strange story of a hitch-hiker. Then he finds out that the story and things that have happened in his own life are very similar. He begins to worry about his wife and young child and that he may be going mad.